78 Cost-effectiveness of intermittent vs. continuous pulse oximetry monitoring in infants hospitalized with stabilized bronchiolitis: A multi-centre clinical trial. (21st October 2022) - Moretti, Myla E; Jegathisawaran, Jathishinie; Wahi, Gita; Bayliss, P; Kanani, Ronik; Sakran, Mahmoud; Pound, Catherine; Parkin, Patricia; Mahant, Sanjay
Abstract: Background: Pulse oximetry is a non-invasive technology that is integral to the supportive care of hospitalized infants with bronchiolitis. A multi-centre, randomized trial comparing the effectiveness of intermittent vs. continuous pulse oximetry found similar hospital length of stay and safety outcomes, and greater nursing satisfaction with intermittent monitoring. Objectives: To evaluate the cost-effectiveness of intermittent vs. continuous pulse oximetry in hospitalized infants with stabilized bronchiolitis. Design/Methods: Prospective economic evaluation concurrent with a randomized trial (October 2016 to May 2019) using a probabilistic analysis. Infants (n=229) 4 weeks to 24 months hospitalized with bronchiolitis, with or without supplemental oxygen, after stabilization were randomized at six Ontario hospitals (community and children's) to intermittent (every 4 hours) vs. continuous pulse oximetry using an oxygen saturation target of 90% or higher. The main outcome measure for the economic evaluation was cost and incremental costs. The clinical effect measure was length of hospital stay in hours. The cost-effective analysis adopted a societal and health care system perspective and a time horizon from hospitalization to 15 days post-discharge. Patient level direct health care costs and indirect costs were included. Costs, health resource use and clinical outcomes were obtained from trial data. Publicly available pricing resources were used to supplement costs. Ranges for sensitivity analysis were based on 95% confidence intervals of the trial data. All costs were reported in 2020 Canadian dollars. This study was funded by a grant from the Canadian Institutes of Health Research. Results: Trial data from 229 infants across six hospitals was included. Mean societal costs per patient were lower in the intermittent monitoring group: $6528 (95% CI: $3201, $12058) in the intermittent and $6815 (95% CI: $1454, $26485) in the continuous group with a mean incremental cost of -$287 (95% CI -$20084, $7842). Mean health care system costs per patient were $3992 (95% CI -$1139, $9224) in the intermittent and $4604 (95% CI -$317, $24126) in the continuous group (incremental cost -$613 (95% CI -$20564, $7089). The mean effect measure, length of stay, was also similar between the two groups: 36.3 hours in the intermittent group and 40.2 hours in the continuous group. One-way sensitivity analyses on all variables revealed that the findings were robust and the incremental costs were not sensitive to the uncertainty within the defined ranges. Conclusion: In a prospective economic evaluation conducted with a clinical trial, we found that intermittent monitoring was less expensive than continuous monitoring, considering societal and health care costs. These findings support recommendations to use intermittent pulse oximetry monitoring in hospitalized infants with stabilized bronchiolitis.